Knowledge Sharing: Understanding the Tension between Practice and Process at Standard Chartered Bank - Castellano, Anna (2005)
The present dissertation looks at intra-firm knowledge sharing as a source of competitive advantage. In particular, it investigates the ways in which knowledge originating from individuals is amplified through sharing and thereby transformed into an organisational asset. Organisations share knowledge through social practice, in the form of informal conversations, networking, and communities of practice, and through the design of processes, such as structures, processes, routines, roles, and procedures. However, practice (the way activities are actually done) and process (the way activities are formally organised) are characterised by conflicting logics. My research explores the tension between practice and process in the context of a global bank. The findings of the study show that the way organisations are designed and the way they are practiced by organisational members affects the way in which knowledge flows and is shared within the work setting. Despite previous studies focus on the role of motivational and knowledge barriers, this research emphasises the importance of structural barriers as main impediments to internal knowledge transfer. My empirical study confirms that practice and process co-exist in knowledge sharing. However, practice is the primary organisational response when firms operate in highly risky environment. In addition, practice-process balancing may provide a more useful concept for organisations willing to leverage knowledge than the widely accepted tacit-explicit dichotomy. Managing the tension between practice and process constitutes a difficult challenge for modern corporations as it involves not only a mechanical conversion of practices into processes, but also a more delicate balancing of identity and efficiency. Finally, the study suggests that developing knowledge strategies that are based on the analysis of practice and process constitutes a different way to think about knowledge management and knowledge sharing in particular.